Dynamics of phytoplankton productivity and exopolysaccharides (EPS and TEP) pools in the Seine Estuary (France, Normandy) over tidal cycles and over two contrasting seasons. (October 2017) - Morelle, Jérôme; Schapira, Mathilde; Claquin, Pascal
Abstract: Exopolysaccharides (EPS) play an important role in the carbon flux and may be directly linked to phytoplankton and microphytobenthos production, most notably in estuarine systems. However the temporal and spatial dynamics of estuarine EPS are still not well understood, nor how primary productivity triggers this variability at these different scales. The aim of this study was to investigate the primary productivity of phytoplankton and EPS dynamics in the Seine estuary over a tidal cycle in three different haline zones over two contrasted seasons. The other objectives was to investigate the origin of pools of soluble carbohydrates (S-EPS) and transparent exopolymeric particles (TEP) in phytoplankton, microphytobenthos or other compartments. High frequency measurements of productivity were made in winter and summer 2015. Physical and chemical parameters, biomass and EPS were measured at hourly intervals in sub-surface waters and just above the water sediment-interface. Our results confirmed that high frequency measurements improve the accuracy of primary productivity estimations and associated carbon fluxes in estuaries. The photosynthetic parameters were shown to be strongly controlled by salinity and by the concentrations of suspended particle matter at the smallest temporal and at spatial scales. At these scales, our results showed an inverse relationship between EPS concentrations and biomass and productivity, and a positive relationship with sediment resuspension. Additionally, the distribution of EPS appears to be linked to hydrodynamics with the tide at daily scale and with the winter at seasonal scale. At spatial scale, the maximum turbidity zone played an important role in the distribution of TEP. Our results suggest that, in the Seine estuary, between 9% and 33% of the S-EPS pool in the water column can be attributed to phytoplankton excretion, while only 0.4%–1.6% (up to 6.14% in exceptional conditions) originates from the microphytobenthos compartments. Most EPS was attributed to remobilization of detrital carbon pools in the maximum turbidity zone and in the sediment or allochthonous origin. Highlights: Accurate estimation of primary productivity in estuaries requires frequent measurements. An inverse relationship found between EPS concentrations and biomass and productivity. Only a minor fraction of the EPS pool was directly attributed to primary production. TEP concentration was strongly controlled by hydrodynamics.